Model Edupreneurship di Pondok Pesantren Asy-Syifa Jepara - Setiawan, Wahid; Subiyantoro, Subiyantoro; Purnama, Sigit (Yayasan Rahmat Islamiyah, 2025)
The purpose of this study is to analyze the concept of edupreneurship, to know the forms of entrepreneurship, to know the impact of edupreneurship on students, graduates, and the community, as well as to analyze the supporting and inhibiting factors for the implementation of edupreneurship at the Asy-Syifa Jepara Islamic Boarding School. This study uses a qualitative approach with descriptive analysis techniques. The data collection method uses structured and in-depth interviews, observation and documentation. Data analysis in the study uses three stages, the first is data reduction. Second, data presentation. Third, drawing conclusions and verification. The results of the study show that the Ash-Syifa Jepara Islamic Boarding School has the concept of edupreneurship which refers to the Qur'an and hadith as well as the characteristics of the Prophet Muhammad (saw) which include sidiq, amanah, tablig, and fathanah. Several forms of entrepreneurship owned by the Asy-Syifa Jepara Islamic Boarding School are divided into 6 fields, namely the food sector, the convection sector, the trade sector, the service sector, the livestock sector and the agricultural sector.